On the Occasion of the Consecration of St. Sava - Јанковић, Живорад (Sabornost - The Theological Year-book, 2013)
Knowledge of the work of Saint Sava, regarding the ways and means of acquiring ecclesiastical independence, arrived gradually. It was possible only after the publication of St Sava’s life by his biographers Domentian (1253) and Theodosius (1300) and are still the source from which one can obtain basic information. It happened just at the beginning of the second half of the 19 century A.D. by the efforts of, in many ways worthy, Duro Daničića in 1860 and 1865. The complexity of the issues at the very beginning of dealing with scientific themes, was already noted by the Russian Church historian Evgenij Golubinski (1871), when he had to choose between the data on the fourteen years of St Sava’s episcopacy, announced in the Domentian’s hagiography, which would be the year 1219, and the reference by the Constantinopolitan Patriarch Germanus II (1222–1240) in relation to that act. For as long as the issue of the (in)correct reference is not resolved, or the lack of a proper reference (depending on how one should look at it) by these two bishops among the Serbian biographers, the consideration of the emergence of the Serbian Church cannot be solved anywhere near.